Physician-Patient Boundaries: Professionalism Training Using Video Vignettes - Judith Lewis; Scott Allan (Association of American Medical Colleges, 2016)
Abstract Introduction The concept of professional boundaries is often not included in medical training. Historically, the field of psychiatry has given much consideration to the topic of boundaries, partially due to the high incidence of sexual boundary violations in psychotherapy practice. And while there is a perception that more formal education is needed in psychiatry, the pressure to adjust the frame of a treatment in clinical practice is ubiquitous. We developed this presentation and discussion, using stimulus videos to depict common boundary issues that crop up in everyday outpatient medical practice. Methods This 90-minute session consists of a 20-minute PowerPoint presentation introducing the concept of professional boundaries and identifies the nine boundary domains as defined by Gutheil and Gabbard. Then the class views and discusses six brief video vignettes (allowing 10 minutes per vignette) with a 10-minute break. Faculty panelists from different specialties and at different stages of training are present to discuss the video vignettes and give examples from their own practice. Results This curriculum was implemented in 2009 at the University of Vermont College of Medicine and has been held annually since. Pre and post data were obtained in March 2009 from third-year medical students who participated in the seminar just prior to beginning their clinical clerkships. Statistically significant changes between pretest and posttest means were observed in five of the 10 questionnaire items, including one knowledge-based question about prescriptions to nonpatients Discussion The two learner groups we targeted were medical students during their clerkship year and residents in their first year of training. However, this material could easily be extended to other disciplines in medicine such as nursing.